STUDY OF EXTRACTION OF COPPER AND IRON IONS FROM TECHNOGENIC SOLUTIONS USING SODIUM DIETHYLDITHIOCARBOMATE - Tashkodirova Rano Erkinjonovna; Sevara Absamatovna Kenjayeva; Khojiev Shokhrukh Toshpulatovich (Modern American Journals, 2025)
This work presents the results of research on the processes of extracting copper (Cu2+) and iron (Fe3+) ions from technogenic solutions formed at the 3rd Hydrometallurgical Plant of the Navoi Mining and Metallurgical Combine. As an extractant, sodium diethyldithiocarbonate NaS2CN(C2H5)2 was used, which has the ability to form stable complex compounds with heavy metal ions. The experiments were conducted at various temperatures (25-45 0C), mixing duration (5-15 min), and dosing of the extractant (5-15 g) in an acidic environment (pH = 4). The degree of extraction was assessed using the PerkinElmer Lambda XLS photoelectric colorimeter. The obtained results showed that under certain conditions (experiment N0. 3), a high degree of copper extraction (99.97%) is achieved, but at the same time, intensive extraction of iron ions (>99.99%) is observed, which indicates a low selectivity of NaS2CN(C2H5)2 in the studied conditions. Graphical analysis confirms that, despite the effectiveness of copper ion removal, the high degree of accompanying iron extraction necessitates the search for additional methods to increase extraction intensity.
Keywords: Technogenic solutions; heavy metals; extraction; copper ions; iron ions; sodium diethyldithiocarbonate; photoelectric analysis; hydrometallurgy; wastewater.